2014
DOI: 10.4103/0973-029x.140729
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ki-67 in normal oral epithelium, leukoplakic oral epithelium and oral squamous cell carcinoma

Abstract: Aims and Objective:To demonstrate the presence, location and pattern of cell proliferation in different histological grades of oral epithelial dysplasia (OED), oral squamous cell carcinoma (OSCC) and normal oral epithelium (NOE) using an antibody directed against the Ki-67 antigen and its intensity of staining evaluated respectively.Materials and Methods:A total number of 100 archival paraffin embedded blocks obtained from Department of Oral and Maxillofacial Pathology were studied. The case details were retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
62
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 30 publications
(42 reference statements)
11
62
3
1
Order By: Relevance
“…The presence of nuclear Ki‐67 was significantly increased in OSCC compared with OED and the control (Table ). It was also greater in OED samples compared with the control, revealing a direct relationship between Ki‐67 immunoreactivity and the grade of malignant cell differentiation and proliferation (Birajdar et al , ; Hasegawaa et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of nuclear Ki‐67 was significantly increased in OSCC compared with OED and the control (Table ). It was also greater in OED samples compared with the control, revealing a direct relationship between Ki‐67 immunoreactivity and the grade of malignant cell differentiation and proliferation (Birajdar et al , ; Hasegawaa et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining with Ki‐67 antibodies is well established as a quick and efficient method to evaluate the antiproliferative profile of neoplasias, as the protein binds to cells undergoing proliferation (Birajdar et al , ). In this study, Ki‐67 immunohistochemical analysis revealed the protein exclusively in the nuclei of OSCC and OED cells, while in controls it was observed more commonly at the basal and parabasal layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Birajdar et al . ; Salvadori et al . ), could be due to the low number of cases in this comparison: 12 cases of WD, 8 cases of MD and 10 cases of PD.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Smita Shrishail Birajdar et al 24 (2014) showed expression of Ki-67 antigen between well differentiated and poorly differentiated OSCC. But in our study, there was Ki-67 expression in all three grades.…”
Section: Discussionmentioning
confidence: 99%